URGENSI KRIMINALISASI TERHADAP PELAKU PENYEDIA JASA FINANSIAL TEKNOLOGI PEER-TO-PEER LENDING ILEGAL (PINJAMAN ONLINE) DALAM HUKUM PIDANA INDONESIA - Benyamin Bangun; Maria Maya Lestari; Elmayanti Elmayanti, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The development of illegal peer to peer lending financial technology inIndonesia has resulted in legal problems experienced by the community asvictims, this is because there is no specific law or regulation that regulates illegalpeer to peer lending financial technology. What was done to overcome this illegalpeer to peer lending financial technology was the blocking of applications,websites carried out by the Investment Alert Task Force together with Kominfo,this blocking sanction was not effective this was due to the ease with which peerto peer lending technology financial applications and websites were created back,while the existing rules, namely POJK No. 77/POJK 01/2016 which regulatestechnology-based lending and borrowing services only applies to peer to peerlending technology financials registered with the OJK so that strict sanctions areneeded in the form of rules or laws that have criminal sanctions in place.This study uses a normative juridical research type, namely research that isfocused on examining the application of the rules or norms in law to legalprinciples. The data collection technique in this research is literature study. Theapproach used in this research is to use a normative approach, namely librarylaw research.The results of the research conducted by the author are, first, criminalizinga peer to peer lending technology financial service provider is urgent/importantthis is because in its implementation activities there are many legal violationssuch as threats, extortion to the dissemination of personal data experienced by thepublic as Second, in overcoming the financial problems of illegal peer to peerlending technology, rules or laws are needed that have criminal sanctions thatcan ensnare this illegal peer to peer lending technology service provider.Keywords: Financial Technology Peer to Peer Lending, Online Loan